S20 Acute cough scale: development of an acute cough symptom severity scale. (December 2018) - Lovegrove, RP; Cho, PSP; Fletcher, HV; Turner, RD; Birring, SS
Abstract : Introduction: Acute cough is a common symptom of upper respiratory tract infections (URTI); a condition with a high health economic impact. There is currently no validated acute cough symptom severity assessment tool. A preliminary Acute Cough Scale (ACS) was developed following focus groups and semi-structured interviews with patients and healthcare professionals. We investigated the internal consistency, responsiveness and concurrent validity of the ACS in a preliminary study. Methods: Participants with URTI of onset <7 days completed the ACS on days 1 and 7 following recruitment. The ACS is a 14-item self-reporting tool with a 6-point Likert scale for each item; higher scores indicating higher severity. Participants also completed a cough severity visual analogue scale (VAS; 0–100 mm) and the quality of life, Leicester Cough Questionnaire-Acute (LCQ-Acute; range 3–21). Results: 28 participants were recruited; mean (SD) age 36.0 (20.0) years, 18 (64%) females. The preliminary ACS items regarding anxiousness and vomiting were removed secondary to floor effects (>60% of responses at minimum response); no significant ceiling effects were observed. The refined ACS consisted of 12 items; none of which had an inter-item correlation >0.8. Internal consistency was high after item reduction: Cronbach's a=0.892. The ACS was able to identify a significant difference in symptom severity between days 1 and 7: mean (SD) ACS scores 19.8 (11.0) vs 12.2 (12.3), p=0.009 (figure 1). The ACS scores on days 1 and 7 were associated with VAS; r=0.553 (p=0.002), r=0.881 (p<0.001); and LCQ-Acute; r=−0.950 (p<0.001), r=−0.932 (p≤0.001), respectively. Discussion: The preliminary results show that the ACS has good internal consistency and is able to detect changes in acute cough symptom severity over 7 days. The ACS has good concurrent validity when compared to the VAS and LCQ-Acute. Further studies in larger populations using psychometric methodology are needed to optimise the measurement characteristics of the ACS.